2004
DOI: 10.1007/s00412-003-0262-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of ancestral chromosome fusion points in the Indian muntjac deer

Abstract: Tandem fusion, a rare evolutionary chromosome rearrangement, has occurred extensively in muntjac karyotypic evolution, leading to an extreme fusion karyotype of 6/7 (female/male) chromosomes in the Indian muntjac. These fusion chromosomes contain numerous ancestral chromosomal break and fusion points. Here, we designed a composite polymerase chain reaction (PCR) strategy which recovered DNA fragments that contained telomere and muntjac satellite DNA sequence repeats. Nested PCR confirmed the specificity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
60
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 33 publications
6
60
1
1
Order By: Relevance
“…These non-telomeric sites of (TTAGGG)n repeats and the colocalization of telomeric repeats and satellite DNA sequences are most likely the result of chromosome rearrangements involving the chromosome ends (including inversions, centric fusion, and telomere-to-telomere fusion) (Go et al, 2000;Li et al, 2000;Lear, 2001;Hartmann and Scherthan, 2004;Ventura et al, 2006;Tsipouri et al, 2008). In addition, sequence analysis of ITSs revealed that the interstitial arrays of (TTAGGG)n repeats could be inserted at intrachromosomal sites through double-strand breaks in ancient chromosomes (Azzalin et al, 2001;Nergadze et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These non-telomeric sites of (TTAGGG)n repeats and the colocalization of telomeric repeats and satellite DNA sequences are most likely the result of chromosome rearrangements involving the chromosome ends (including inversions, centric fusion, and telomere-to-telomere fusion) (Go et al, 2000;Li et al, 2000;Lear, 2001;Hartmann and Scherthan, 2004;Ventura et al, 2006;Tsipouri et al, 2008). In addition, sequence analysis of ITSs revealed that the interstitial arrays of (TTAGGG)n repeats could be inserted at intrachromosomal sites through double-strand breaks in ancient chromosomes (Azzalin et al, 2001;Nergadze et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Large ITSs usually originate after the occurrence of chromosome rearrangements, especially Robertsonian (Rb) translocations, which result after loss of the chromosome end protection in telocentric chromosomes, allowing the fusion of two chromosomes and thus producing a neo-metacentric chromosome that may or may not retain telomeric sequences in the newly formed centromere (Garagna et al 1995;Bouffler 1998). When the telomeric repeats are maintained, they result in ITSs (Hsu et al 1975;Simons and Rumpler 1988;Meyne et al 1990;Garagna et al 1997;Hartmann and Scherthan 2004). Indeed, ITSs are mostly located at the pericentromeric regions of neometacentric chromosomes and, after the Rb fusion, they undergo amplification, allowing the stabilization of the neo-centromere through the formation of pericentromeric heterochromatin (Ruiz-Herrera et al 2008;Rovatsos et al 2011).…”
mentioning
confidence: 99%
“…The most well-known hypothesis is the tandem fusion hypothesis, first proposed by Hsu et al (1975), suggesting that the 2n = 6♀/7♂ karyotype of M. muntjak vaginalis could have evolved from 2n = 46 M. reevesi-like ancestral karyotype through extensive tandem fusions and several centric fusions. Subsequent studies, including conventional comparative cytogenetics (Shi et al, 1980;Elder & Hsu, 1988;Fontana & Rubini, 1990), chromosome painting (Yang et al, 1995(Yang et al, , 1997aYang, 1998;Chi et al, 2005a;Huang et al, 2006a), FISH mapping of centromeric sequences, telomeric sequences, cosmid clones and BAC clones (Scherthan,1990;Lin et al, 1991;Lee et al, 1993;Li et al, 2000a;Hartmann & Scherthan, 2004;Chi et al, 2005b;Huang et al, 2006b), and combined chromosome painting and satellite DNA mapping (Scherthan, 1995;Yang et al, 1997b,d;Huang et al, 2006c), provided direct evidence for the tandem fusion hypothesis. The chromosomal mechanism underlying the karyotype evolution in Muntiacus is well-established now: the karyotypes of all extant muntjacs have evolved from a common ancestor with a 2n = 70 acrocentric karyotype by extensive centromere-telomere fusions and several centric fusions.…”
mentioning
confidence: 99%
“…Some studies suggested that the repetitive DNA families at or near the centromeric and telomeric regions might facilitate illegitimate recombination between non-homologous chromosomes of muntjacs (Brinkley et al, 1984;Bogenberger et al, 1985Bogenberger et al, , 1987Benedum et al, 1986;Lin et al, 1991Lin et al, , 2004Lee et al, 1994Lee et al, , 1997Scherthan, 1995;Lee & Lin, 1996;Yang et al, 1997b;Li et al, 2000aLi et al, , b, 2002Hartmann & Scherthan, 2004). At present, four satellite DNA families are found in Muntiacus: satellite DNA families I, II, IV and V (Bogenberger et al, 1985;Lin et al, 1991Lin et al, , 2004Li et al, 2000bLi et al, , 2005.…”
mentioning
confidence: 99%